2007
DOI: 10.1002/cne.21578
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of LIM‐domain transcription factors is coincident with delayed maturation of photoreceptors in the chicken retina

Abstract: In the retina of warm-blooded vertebrates, photoreceptors are specified many days before the onset of synaptogenesis and the expression of photopigments. The factors that regulate the maturation of photoreceptors in the developing retina remain unknown. We report here that photoreceptors transiently express LIM-domain transcription factors during the development of the chicken retina. We examined the differentiation of photoreceptors through the normal course of embryonic development and at the far periphery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 66 publications
(111 reference statements)
3
81
0
Order By: Relevance
“…Lim3 (Lhx3) is specifically expressed by postmitotic bipolar cells in the developing chick retina (Edqvist and Hallb€ o€ ok, 2004) and in a subset of bipolar cells in the mature mouse retina (Kim et al, 2008). Fischer et al (2008) have shown that Lim3 and Islet-2 (Isl2) are transiently expressed by differentiating photoreceptors in the developing chick retina. Isl2 is also expressed by ganglion cells in the retina (Edqvist et al, 2006) and contributes to the guidance of retinal ganglion cell axons (Pak et al, 2004).…”
Section: Lim-hd Transcription Factors and Development Of The Retinamentioning
confidence: 98%
See 2 more Smart Citations
“…Lim3 (Lhx3) is specifically expressed by postmitotic bipolar cells in the developing chick retina (Edqvist and Hallb€ o€ ok, 2004) and in a subset of bipolar cells in the mature mouse retina (Kim et al, 2008). Fischer et al (2008) have shown that Lim3 and Islet-2 (Isl2) are transiently expressed by differentiating photoreceptors in the developing chick retina. Isl2 is also expressed by ganglion cells in the retina (Edqvist et al, 2006) and contributes to the guidance of retinal ganglion cell axons (Pak et al, 2004).…”
Section: Lim-hd Transcription Factors and Development Of The Retinamentioning
confidence: 98%
“…Fischer et al, 2008 Isl1 immunoreactivity in the developing retina -Isl1 is not expressed by differentiating photoreceptors.…”
Section: The Lim-homeodomain Islet-1 Transcription Factormentioning
confidence: 99%
See 1 more Smart Citation
“…21 Although the level of Lhx3 was slightly decreased in the Foxp1-CKO lens in the microarray, Foxp1 is known to suppress Lhx3 expression and promote Hox6, 9, or 10 in motor neurons, 30 In the retina, Lhx3 promotes the expression of genes that are involved in the early stages of differentiation, but may suppress the expression of genes that are required in mature photoreceptors in chicken retina. 31 In addition, although the involvement of these particular members of Hox in retinal and lens development had not been reported, these molecules are candidates to clarify mechanisms of roles of Foxp1 in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, LIM homeodomain proteins LHX3 and ISL1 synergize with bHLH transcription factors to specify motor neuron subtype identity in the embryonic spinal cord [16]. In the chicken retina, photoreceptors transiently express LIM homeodomain proteins during development, before the onset of synaptogenesis and expression of terminal differentiation marker genes such as those encoding photopigments [17]. Besides, conditional inactivation of Isl1 in the primordium of the neural retina leads to a significant reduction in bipolar, cholinergic amacrine and ganglion cells [18].…”
Section: Introductionmentioning
confidence: 99%